Pemilu Di Kecamatan Pameungpeuk Kabupaten Bandung - Faturohman, Adit Abil; Fatah R., Jundi; Ilham, Septino (UIN Sunan Gunung Djati Bandung, 2025)
The election in Pameungpeuk Subdistrict, Bandung Regency, reflects significant local political dynamics despite its relatively small number of polling stations (TPS) and voter population compared to other subdistricts. This study employs a qualitative approach with descriptive data analysis to examine the election process, voter political preferences, and the challenges faced during the election. The findings show that public enthusiasm was relatively high, although logistical challenges such as road access and weather affected the distribution of election materials. Voter preferences in Pameungpeuk were influenced by local needs, promises of infrastructure development, as well as emotional and personal connections with the candidates. Support from election committees and supervisors ensured the smooth running of the voting process, despite a shortage of personnel in some polling stations. The implications of the election results highlight the critical role of rural areas like Pameungpeuk in determining the outcomes of elections at the regency level.